The effects of trastuzumab on HER2-mediated cell signaling in CHO cells expressing human HER2 - Hamid Maadi; Babak Nami; Junfeng Tong; Gina Li; Zhixiang Wang (BMC Cancer, 2018)
Abstract Background Targeted therapy with trastuzumab has become a mainstay for HER2-positive breast cancer without a clear understanding of the mechanism of its action. While many mechanisms have been suggested for the action of trastuzumab, most of them are not substantiated by experimental data. It has been suggested that trastuzumab functions by inhibiting intracellular signaling initiated by HER2, however, the data are very controversial. A major issue is the different cellular background of various breast cancer cells lines used in these studies. Each breast cancer cell line has a unique expression profile of various HER receptors, which could significantly affect the effects of trastuzumab. Methods To overcome this problem, in this research we adopted a cell model that allow us to specifically examine the effects of trastuzumab on a single HER receptor without the influence of other HER receptors. Three CHO cell lines stably expressing only human EGFR (CHO-EGFR), HER2 (CHO-K6), or HER3 (CHO-HER3) were used. Various methods including cytotoxicity assay, immunoblotting, indirect immunofluorescence, cross linking, and antibody-dependent cellular cytotoxicity (ADCC) were employed in this research. Results We showed that trastuzumab did not bind EGFR and HER3, and thus did not affect the homodimerization and phosphorylation of EGFR and HER3. However, overexpression of HER2 in CHO cells, in the absence of other HER receptors, resulted in the homodimerization of HER2 and the phosphorylation of HER2 at all major pY residues. Trastuzumab bound to HER2 specifically and with high affinity. Trastuzumab inhibited neither the homodimerization of HER2, nor the phosphorylation of HER2 at most phosphotyrosine residues. Moreover, trastuzumab did not inhibit the phosphorylation of ERK and AKT in CHO-K6 cells, and did not inhibit the proliferation of CHO-K6 cells. However, trastuzumab induced strong ADCC in CHO-K6 cells. Conclusion We concluded that, in the absence of other HER receptors, trastuzumab exerts its antitumor activity through the induction of ADCC, rather than the inhibition of HER2-homodimerization and phosphorylation.